The Nephroprotective Role of Carnosine Against Ifosfamide-Induced Renal Injury and Electrolytes Imbalance is Mediated Via the Regulation of Mitochondrial Function and Alleviation of Oxidative Stress - Ommati, Mohammad Mehdi; Farshad, Omid; Ghanbarinejad, Vahid; Mohammadi, Hamid Reza; Khadijeh, Mousavi; Negar, Azarpira; Zahra, Mahboubi; Ilkhaninasab, Farshid; Moezi, Leila; Heidari, Reza (Drug Research, 2020)
Background Ifosfamide (IFO) is an alkylating agent administered against different types of malignancies. Several cases of renal injury and serum electrolytes disturbances have been reported in IFO-treated patients. Oxidative stress and mitochondrial dysfunction are suspected of being involved in the mechanism of IFO nephrotoxicity. Carnosine is a dipeptide which its antioxidant and mitochondria protecting properties have been mentioned in different experimental models. The current study aimed to evaluate the nephroprotective properties of carnosine against IFO-induced renal injury.Methods Rats were treated with IFO (50 mg/kg, i.p) alone or in combination with carnosine. Serum and urine biomarkers of renal injury in addition to kidney markers of oxidative stress were evaluated. Moreover, kidney mitochondria were isolated, and some mitochondrial indices were assessed.Results Elevated serum creatinine and BUN, hypokalemia, and hypophosphatemia, in addition, to an increase in urine glucose, protein, γ-GT, and alkaline phosphatase (ALP), were evident in IFO-treated animals. IFO also caused an increase in kidney reactive oxygen species (ROS) and lipid peroxidation (LPO). Renal GSH levels and antioxidant capacity were also depleted with IFO therapy. Mitochondrial dehydrogenase activity, GSH level, membrane potential, and ATP content were decreased while mitochondrial LPO and permeabilization were increased in IFO group. Carnosine (250 and 500 mg/kg, i.p) mitigated IFO-induced oxidative stress and mitochondrial impairment in renal tissue.Conclusion Our data suggest mitochondrial dysfunction and oxidative stress as fundamental mechanisms of renal injury induced by IFO. On the other hand, carnosine supplementation protected kidneys against IFO-induced injury through regulating mitochondrial function and mitigating oxidative stress.
Keywords: antioxidants/NO pathways drugs; biomarkers; endocrine pharmacology; toxicology; adverse drug reactions; pharmacology; drug metabolism; apoptosis; gastrointestinal pharmacology; non-specific cation channels; experimental pharmacology; cardiovascular pharmacology; cellular signal transduction by receptors and ion channels; renal pharmacology; biologics; peptide; energy metabolism; Fanconi syndrome; mitochondria; nephrotoxicity; oxidative stress